Implementasi Aturan Terkait Pembukaan Rekening Nasabah (Studi Kasus PT Bank Central Asia Tbk) - Lesmana Lubis, Rendy; Machmud, Aris (UNES Law Review, 2023)
Opening a savings account, a common practice in modern society, is subject to specific bank requirements, including the criterion of adulthood regulated by Indonesian law. This juridical research navigates challenges such as legal disparities and regulatory changes related to the criteria for opening savings accounts. Ethical considerations and consumer protection play a pivotal role in determining adulthood criteria, contributing to a nuanced understanding of the legal aspects of banking transactions. The study provides insights for banks to adapt account opening policies to Indonesia's evolving legal landscape. Despite technological advancements in the banking sector, compliance with account opening requirements remains crucial. The study sheds light on legal aspects, particularly digital identification and identity verification in the context of savings account opening. Legal frameworks such as Law No. 19 of 2016 and Bank Indonesia's regulations underpin the review of savings account opening requirements, addressing consumer protection and banking transaction security. Relevant to the banking industry's current technological landscape, this research aids regulatory compliance and fosters consumer trust in digital banking services. The study offers insights into how technology shapes savings account opening requirements, providing a foundation for enhancing banking policies in the digital era.